Road Safety Audit for Highways - Rodríguez Mora, Marcos E. (2025)
What is a Road Safety Audit? It is a technical evaluation carried out by a team of auditors specialized in road and bridge safety, aimed at identifying infrastructure-related factors that may contribute to traffic accidents or increase their severity, as well as conflicts in the operation of vehicles and other road users.